Plan de gestión administrativa y financiera para la veterinaria Pet Shop-Pets Planet - Bastidas Guevara, Pedro Josue (2022)
A study was conducted on financial management in the veterinary health sector due to the lack of effective financial management in the veterinary Pet Shop-Pets Planet, the economic imbalance due to ignorance of vulnerability and financial scarcity. Resource planning and control. The purpose of the study is to analyze financial management by diagnosing the current state of the sector and study the financial statements to propose a model that can improve the profitability of animal health companies that face these vulnerabilities commercial. A mixed approach was used for the development of tasks and the types of study used were descriptive. In terms of time span, the company was longitudinal because it was studied for several economic periods. The population went to veterinary workers. Data collection techniques include interviews, observation guidelines and analysis of financial statement documents.............